Fixed Point Theorems for $ψ$-contractions in S-metric Spaces and KKS-metric Spaces - K. P. R. Sastry; K. K. M. Sarma; P. Krishna Kumari; Sunitha Choudari (International Journal of Mathematics And its Applications, 2017)
In this paper we introduce the notion of $ψ$-contractions for self maps on S-metric spaces and establish a fixed point theorem for such maps. We also introduce a new subclass of S-metric spaces called KKS metric spaces and prove a fixed point theorem for a $ψ$-contraction on a KKS metric space. An open problem is also given at the end of the paper.